System requirements for a computerised patient record information system at a busy primary health care clinic - PJ Blignaut; T McDonald; CJ Tolmie (AOSIS, 2001)
A prototyping approach was used to determine the essential system requirements of a computerised patient record information system for a typical township primary health care clinic. A pilot clinic was identified and the existing manual system and business processes in this clinic was studied intensively before the first prototype was implemented. Interviews with users, incidental observations and analysis of actual data entered were used as primary techniques to refine the prototype system iteratively until a system with an acceptable data set and adequate functionalities were in place. Several non-functional and user-related requirements were also discovered during the prototyping period.